Analysing regional sustainability through a systematic approach: The Lombardy case study - Pietro Caratti; Ludovico Ferraguto (Fondazione Eni Enrico Mattei (FEEM), 2008)
The intrinsic complexity of the sustainability concept challenges research towards more sophisticated ways to model and assess the dimensions underlying it. However, currently adopted modelling techniques and indicators frameworks are not able to give an integrated assessment through the different components of sustainability, providing incomplete visuals of the reality that they aim to catch. This paper tries to assess how the INSURE methodology can provide a contribution in the analysis of sustainability through indicator frameworks, describing its application to the Lombardy region (Italy). Developed on the course of a 6th European Framework Program financed project to measure sustainability in the European regions, the methodology provides two distinct sustainability representations, based on a quantitative 'top-down' System Dynamics model and on a qualitative 'bottom-up' System Thinking approach. The models are then linked to a hierarchical indicator framework setting policy priorities. The overall objective is thus to create a set of regional indicators, adapting the models of regional sustainability to different policy agendas. The purpose of the paper is twofold: defining a new approach to sustainability appraisal, and assessing how the Region is holistically behaving towards sustainable development. Starting from a basis analysis of the main shortcomings highlighted by the use of most adopted methodologies, the paper will verify the contribution given by the INSURE methodology to research in the fields of modelling and indicators approaches, providing insights over methodological adjustments and the results obtained from the application to Lombardy. The conclusions will show how the methodology has tried to overcome identified constraints in current models, like the strong dependence on existing datasets of the obtained representations, the under-coverage of 'immaterial factors' role and the scarce integration between sustainability dimensions.
Keywords: Q01; R; R15; O2; O18; 330; Sustainable Development; Regional Economics; Econometric and Input Output Models; Development Planning and Policy; Regional Analyses; Regionale Entwicklung; Regionalpolitik; Nachhaltige Entwicklung; Input-Output; Regionalforschung; Lombardei